Outcomes of daytime nurse practitioner–staffed versus resident-staffed nonsurgical intensive care units: A retrospective observational study. Issue 6 (November 2022) - Liao, Min-Tsun; Chang, Hsiao-Chi; Chen, Chun-Kai; Cheng, Li-Ying; Lin, Ting-Tse; Keng, Li-Ta
Abstract: Background: Rapid developments in medical care—such as monitoring devices, medications, and working hours restrictions for intensive care personnel—have dramatically increased the demand for intensive care physicians. Therefore, nurse practitioner (NP)–staffed care is becoming increasingly important. This study was aimed to compare the outcomes of daytime NP-staffed and daytime resident-staffed nonsurgical intensive care units (ICU). Methods: We retrospectively assessed patients admitted to a nonsurgical ICU from March 2017 to December 2017. We collected basic patient data, including age, sex, admission diagnosis, transferring unit, and Acute Physiology and Chronic Health Evaluation II (APACHE II) score. Primary endpoints were ICU mortality, hospital mortality, and 30-day mortality. Secondary endpoints were 48-h readmission, discharge to nonhome locations, and lengths of ICU and hospital stay. Results: A total of 838 subjects were analysed: 334 subjects in the NP-staffed group and 504 in the resident-staffed group. The NP-staffed group was more likely to come from inpatient units (38.3% vs 16.5% for resident-staffed group; p  < 0.001) and had lower disease severity (APACHE II score, 13.9 ± 8.4 vs 15.1 ± 8.2 for resident-staffed group; p  = 0.047). After adjusting for age, sex, location before ICU admission, APACHE II score, and significantly different basic characteristics, there were no differences in ICU mortality, hospital mortality, or 30-day mortality between the two groups. Secondary analysis showed the NP-staffed group had a lower discharge rate to nonhome locations (2.1% vs 6.3%; p  = 0.023) and shorter hospital stay (12.1 ± 14.1 vs 14.2 ± 14.3 days; p  = 0.015). Conclusions: We observed no difference in mortality between daytime NP-staffed and resident-staffed nonsurgical ICUs. Daytime NP-staffed care is an effective, safe, feasible method for staffing nonsurgical ICUs.